(untitled) (Journal of Ideas in Health, 2025)
Background: Climate change, no doubt, acts as a catalyst for the spread of infectious diseases in Nigeria’s rural communities by altering the habitats of vectors such as mosquitoes and ticks. The study aims to evaluate the effectiveness of communication strategies to raise awareness about NTDs in the context of climate change among rural communities. Methods: The study adopted the convergent parallel mixed research design method. It was 2025 research carried out in six states of North Central, Nigeria plus the Federal Capital Territory (FCT), Abuja. A four-point Likert scale questionnaire was used as instrument in the collection of quantitative data from 365 respondents in the communities. While interview guide was used as the instrument to collect data from 21 key informants comprising of community leaders, health care givers, and policy makers. Data was analyzed using descriptive statistics and thematic analysis. Results: Participants from 18 to 56 years and above took part in the study. They constitute 168 male and 197 female. Those with secondary school education were more than those without education, and those with primary school certificates. Findings revealed that participants in the study understood adverse variation in climate connects to disease and public health problems. In addition, participants in the study unanimously agreed (with a mean score of 3.00 and above) that combating NTDs require a participatory approach, which must involve all relevant stakeholders. Conclusion: Empirical studies on NTDs in Nigeria and other endemic regions show that regardless of government and health institutions efforts toward the mitigation of NTDs, awareness is still a challenge. Therefore, increased sensitization and public involvement are essential policy priorities to sustain progress in NTDs elimination in Nigeria’s rural communities.